Methods for Growing Spirillum lipoferum and for Counting It in Pure Culture and in Association with Plants - Okon, Yaacov (1977)
Methods are described for growing Spirillum lipoferum in quantities sufficient to serve as inoculant in field trials of its associative N(2)-fixing ability with higher plants and as a source of cells for the preparation of nitrogenase, cytochromes, respiratory enzymes, etc. A heavy inoculum of S. lipoferum grown on NH(4)(+) was transferred to a medium of minimal nitrogen content, and initial rapid growth at the expense of residual combined nitrogen was replaced later by slower growth on N(2). Conversion to N(2) fixation was prompt upon exhaustion of fixed nitrogen; growth on N(2) was most rapid at a pO(2) of 0.005 to 0.007 atm. Numbers of S. lipoferum can be estimated by diluting soil, crushed roots, or other material, and inoculating diluted samples into a stagnant semisolid medium. Development of a characteristic subsurface layer of organisms and demonstration the these organisms can reduce C(2)H(2) are presumptive evidence that they are S. lipoferum. With most-probable-number tables the observations can be converted to numbers of S. lipoferum in the samples. The most-probable-number method indicated that numbers of S. lipoferum may increase 100-fold or more in roots of maize removed from the plant and incubated for 24 h at 30°C at a pO(2) initially adjusted to 0.01 atm.